Pengenalan Fitur Free Pickup Service Pada Aplikasi “PosAja” Sebagai Upaya Mempermudah Masyarakat Dalam Mengirim Paket - Bagus Susanto; Fani Khoirotunnisa (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Seeing the competition in the business market world is getting tighter, PT. Pos Indonesia (Persero) which provides goods or mail delivery services if it does not innovate it will be less competitive, currently PT. Pos Indonesia (Persero) is ranked number 3 nationally in the national ranking of services. Free pickup servive service or free package pick-up is an effort made by PT. Pos Indonesia (Persero) so that customers do not go to other delivery services. The PosAja Indonesia application has great potential with various services provided, but the concern of the Indonesian people for the PosAja application is still lacking because of a number of problems, including PosAja is still fairly new, so the author is very interested in introducing the application as a form of community service with the title "The introduction of the free pickup service feature in the PosAja application as an effort to make it easier for people to send packages". Application introduction activities are carried out through Instagram social media by distributing posters addressed to all Indonesian people. The community service period starts on December 14 – 18, 202. For technical implementation, it starts from planning, action, and evaluation. The results of the introduction of the PosAja application through Instagram received a positive response from the public, and simply added information to the community. With the introduction of the PosAja application, it is expected that users of this application will increase. The introduction of the free pickup service feature of the PosAja application is expected that the public can know the existence of the Pos Aja application so as to increase the adoption of the PosAja application.